PROVENANCE AND DISTRIBUTION OF MIDDLE BAONG SAND IN THE MALACCA STRAIT AND ITS SURROUNDING - Totong Koesnadi Usman; Yoga Andriana Sendjaja; Nurdrajat Nurdrajat (BULLETIN OF THE MARINE GEOLOGY, 2023)
The Middle Baong Sand Formation has long been ascribed to the Malay Peninsula. However, this contradicts the results of chronostratigraphic correlation and rare earth element (REE) analysis, which indicate another source from the south. This research was conducted in North Sumatra, especially in Pertamina's onshore and offshore work areas. The comparison area is located in Kutacane-Karo and the Malay Peninsula. The objective of the study is to understand the provenance of the Middle Baong Sand Formation in North Sumatra. Data from four wells and 32 outcrops are used to evaluate the provenance and distribution of Middle Baong Sand in the study area. Besides that, secondary data from three outcrops are also used to support the analysis. The methods used in this study are chronostratigraphic correlation and REE analysis. The results showed that the provenance of the Middle Baong Sand onshore is estimated to originate from southwest Sumatra, contrary to general assumptions. Validation was carried out by comparing Malay Peninsula data with Kutacane research data and wells using REE analysis. The analysis results showed that the Middle Baong Sand Formation in the onshore area has a different provenance from the Middle Baong Sand Formation in the offshore area, which contradicts other research conducted so far. Based on this study, it is concluded that the paleogeography of the North Sumatra basin undergoes deepening symmetrically in the central basin since 10.46 million years ago (Mya).